Integrasi Nilai Akhlak dalam Dinamika Pembelajaran PAI di Ruang Kelas - Hairun Hasanah Sagala; Muhammad Hasan Nasution (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
Islamic Religious Education (PAI) plays a crucial role in shaping students' personality and morals, not only by imparting religious knowledge but also by internalizing moral values for everyday life. The rapid development of technology, globalization, and social change presents challenges to moral development, requiring PAI learning to effectively integrate moral values in classroom dynamics. This study aims to examine the integration of moral values in PAI learning and its implications for strengthening character education. Using a qualitative approach with library research, data were gathered from books, journal articles, and previous studies on PAI and moral education. Data collection was through documentation, and content analysis was used to synthesize concepts, theories, and findings. The study finds that moral values in PAI learning are integrated through two approaches: explicit and implicit. Explicit integration involves teaching materials containing moral values, while implicit integration occurs through teacher role models, humanistic interactions, classroom management, and participatory and contextual learning methods. The integration of moral values enhances the meaning of PAI learning and contributes to students' attitudes and behavior. This study highlights that well-designed, value-oriented PAI learning plays a vital role in strengthening character education and continuously fostering students' morals.